Kutaisi State Youth Dance Ensemble In The XX 50-60s - Khatchapuridze, Luiza (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2018)
Kutaisi ensemble of Georgian folk dance was founded by the famous choreographer Murman Lomtatidze in 1945-1950. Director was the former brilliant dancer Shalva Iashvili. The ensemble contained the youth from Kutaisi with different professions who were deeply fallen in love with dancing. The first concert of the ensemble was held at the opening ceremony of the Lado Meskhishvili drama theatre on November 5, 1955. The first responsible performance was in Tbilisi, 1957 during the first republic student festival. Win in the competition gave the laureate title to the ensemble. In 1958 they started the inner tour with the following route: Batumi, Lanchkhuti, Ozurgeti, Zugdidi, Abasha, Martvili, Sokhumi, New Aton, Gali, Okumi, Mokvi, Ochamchire. In 159 they went for the tour in South Georgia. The ensemble enjoyed great love and popularity, which was proved by Anshlag at their concerts. In 1960 the ensemble went to Moscow and in the same year, they visited the republics of the Soviet Union. In 1961 they visited Europe (Hungary, Germany, Poland, Bulgaria, Romania, France). It should be noted that the dances had ethnographic nature thus they effectively served the introduction of Georgian culture at foreign lands. We can promulgate that the Kutaisi state youth dance ensemble of the 50-60s of the previous century wrote the name of Kutaisi in the history of Georgian dance with golden letters.